Perspektif Capu Reke (Batal Nikah) Setelah Paluk Kila (Tukar Cincin) dalam Hukum Adat Perkawinan Manggarai - Matilda Fidrisa Anggun; Sukardan Aloysius; Petornius Damat (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The purpose of this research is to analyze the perspective of capu reke (void marriage) after paluk kila (exchange of rings) in Manggarai Marriage Customary Law. This type of research is empirical normative legal research. The sources of legal materials used in this research are primary and secondary legal materials. The method of processing legal materials through 3 (three) stages, namely editing, coding and systematization of data which is then analyzed descriptively qualitative. The results of this study found that: (1) The meaning of capu reke (capu = eliminate, cancel, break and reke = promise) which is literally interpreted as eliminating or breaking promises with other parties. Paluk kila (paluk = exchange; kila = ring). The Manggarai indigenous people interpret this paluk kila as being known to the extended families of both parties, as well as an acknowledgment from the tongka (witness/spokesperson) that the couple is true and ready to become a woe nelu (new family). (2) The perspective of capu reke (void marriage) after paluk kila (exchange of rings) in this ceremony is very sacred and from this problem the traditional ritual which is considered very magical and highly respected seems to be played with. (3) The legal consequences and customary sanctions that arise are: If the man decides first, the sanction is that the man must pay or cover the woman's shame in the form of saung leba (money) with a buffalo (kaba ngalu tau rangga). If, on the other hand, the woman decides first, the sanction is to give twelve Manggarai traditional cloths and one podo wa'u pig (returning the male clan). The legal consequences that arise are also the status of the child in this capu reke event who has the right to take care of the father (lut wa'u) and get inheritance rights from the father even though the custody is in the mother. The suggestions for the results of this study are (1) It is better if the marriage promise that is later denied or canceled is regulated more clearly in the law, even the rules must be clearer about the marriage promise and the legal consequences of the agreement that was made before the marriage. (2) Prospective couples are required to make a marriage agreement in order to better understand all the consequences that will be accepted after the marriage agreement takes effect between them.